Analysis of General Chemistry Teaching and Learning Resources: Department of Agro-technology University of Medan Area - Anggraini, Fitri; Matondang, Silvia Elastari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to describe how the teaching materials related to chemical in the curriculum of the Department of Agro-technology Medan Area University. For the purpose of observation, interviews and giving questionnaires to various stakeholders in the Department of Agro-technology University Medan Area. Results obtained in the form of retribution subjects related to chemistry as much as 7 subjects with a weight of 20 credits or as much as 13.8 % of the total of 145 credits. Those subjects are General Chemistry, Biochemistry Agriculture, Basic Soil Science, Soil Fertility and Fertilizer, Seed Technology, Post-Harvest Technology and Advanced Plantation Crops.